Extraction of Organic Compounds From Lacustrine Oil-Prone Shales and the Effect on Nanopore - Cao, Huairen; Zhang, Deping; Wang, Xiaoyu; Fu, Deliang (Frontiers in Earth Science, 2022)
Lacustrine oil-prone shale at oil-generation stage develops a large number of nanopores; however, influence of fluid-shale interactions on the nanopores of lacustrine shale is poorly understood. A suite of mature lacustrine shales from the Songliao Basin Qingshankou Formation was performed on sequential organic solvent (petroleum ether and mixture of dichloromethane and methanol) extractions, and nitrogen and carbon dioxide adsorptions, Rock-eval pyrolysis and Field Emission Scanning Electron Microscopes (FE-SEM) observation. The sequential extractions show decreases in total organic matter (TOC) and in exacted organic matters (EOMs) content of the shale, but increases in specific area (SBET) and pore volume of the extracted residues. Before and after extractions, the relationships between amount extracted OM and SBET, pore volume and their cumulative increments reveal the OM as a main factor affecting the development of nanopores in these shales. The reasons are (i) SBET and mesopores are mainly blocked by EOMs in the initial samples, (ii) the cumulative increases of SBET and mesopores are dominantly controlled by amount extracted hydrocarbons during petroleum ether extraction and (iii) both hydrocarbons and NSOs (resins and asphaltenes) have an influence on cumulative increases of SBET and mesopores, and kerogen exposed more open porous-organic mesopores after the EOMs in the extracted shales. Here further concludes that oils adsorbed on pore surfaces are dominantly distributed on nanopores less than 10 nm, and free oils occur when threshold of average pore width in studied shales is over 11.7 nm.